Phylogeny of Najas (Hydrocharitaceae) revisited: Implications for systematics and evolution. Issue 2 (23rd February 2017) - Ito, Yu; Tanaka, Norio; Gale, Stephan W.; Yano, Okihito; Li, Jie
Abstract: Najas (Hydrocharitaceae) is a cosmopolitan genus of 30‐40 species of aquatic plants. While an infrageneric subdivision into two subgenera is generally accepted, various sectional classifications proposed in subg. Caulinia have been controversial. Earlier analyses identified tropical Asia, which harbors more than one‐third of all species, as the area of origin for the genus, but this inference requires re‐evaluation using worldwide taxon sampling. Polyploidy has been widely observed in the genus but its correlation with phylogeny has yet to be explored. Here we applied a molecular phylogenetic approach using balanced taxon sampling (1) to test infrageneric classifications, (2) to re‐assess biogeographic origin, and (3) to explore whether and how polyploidy characterizes evolutionary lineages. Our analyses of plastid and nuclear (ITS) DNA datasets produce largely congruent results that recover the two subgenera but find little support for most sectional classifications. To overcome this shortfall, we propose a new sectional classification of subg. Caulinia. The previously inferred tropical Asian origin of the genus is rejected and, instead, North America is discerned as the ancestral area, implicating dispersal of the most recent common ancestor of Najas and its sister genera in Hydrocharitaceae from tropical Asia. Based on chromosome counts confirmed in the present study and those compiled from literature, the role of polyploidization in the evolution of Najas is shown to be relatively limited, in contrast to the extreme infraspecific chromosome variation previously reported.